Association of 25(OH)D serum level with biological aging: A Cross-Sectional Study of 2007–2016 NHANES surveys - Yi Feng; Licheng Yu; Jue Wang (PLoS ONE, 2025)
Vitamin D plays a crucial role in various aspects of human body, including aging, but chronological age may not accurately reflect the true biological aging status. Recently, PhenoAge has been developed to estimate an individual’s biological age based on different biological and clinical measures. Therefore, we investigated the relationship between 25(OH)D serum levels and biological aging calculated by PhenoAge Acceleration (PhenoAgeAccel) using data from the 2007−2016 National Health and Nutrition Examination Survey (NHANES). 25(OH)D serum levels were negatively associated with PhenoAgeAccel (β = −0.04 standard deviation [SD]; 95% confidence interval [CI]: −0.08 to 0.00). This negative association was dose-dependent in females (β = −0.07 SD; 95% CI: −0.12 to 0.01), but not in males. Generalized additive models further revealed gender-specific non-linear patterns: a U-shape pattern in males but an L-shaped pattern in females. Using segmented regression to confirm inflection points, we observed that 25(OH)D serum levels were linked to reduced PhenoAgeAccel at levels below 38.2 nmol/L (15.3 ng/mL) in males (β = −0.013 SD; 95% CI: −0.025 to −0.002) and 62.5 nmol/L (25.0 ng/mL) in females (β = −0.007 SD; 95% CI: −0.01 to −0.004,). However, 25(OH)D serum levels above 125 nmol/L showed no association with PhenoAgeAccel in females (β = −0.001 SD; 95% CI: −0.005–0.002), while in males, elevated levels (>91.6 nmol/L) were associated with increased PhenoAgeAccel (β = 0.005 SD; 95% CI: 0.002–0.008). Our findings indicate that vitamin D insufficiency has an inverse link with accelerated biological aging, and high levels of vitamin D in males accelerated biological aging as well, offering valuable insights into the relationship between vitamin D and biological aging.